PERKEMBANGAN MANAJEMEN RISIKO DI MAN 2 MODEL PADANGSIDIMPUAN - Nur Apnilelawati; Fachruddin Azmi (MES: Journal of Mathematics Education and Science, 2022)
This study aims to describe the development of risk management in MAN 2 Padangsidimpuan Model. Risk management aims to manage these risks so that we can obtain the most optimal results. In this study, researchers used descriptive research methods. This research method is a method that seeks to reveal the facts of an event, object, activity, process, and human as it is at the present time or a period of time that is still possible in the respondent's memory. The research location is at MAN 2 Model Padangsidimpuan which is located at Jalan Sutan Soripada Mulia No. 29. The results show that the development of risk management in MAN 2 Padangsidimpuan Model is the entire Madrasa risk management process that must be monitored, and if necessary modifications are made. In this way, the system can react dynamically, changing according to existing conditions. Monitoring is carried out through ongoing management activities, separate evaluation of the Madrasah risk management process is a combination of the two.